Mathematical Models of Biological Control of Dengue - Kumar, Nand Kishor; Yadav, Dipendra Prasad (Darul Yasin Al Sys, 2024)
Dengue fever, transmitted by Aedes mosquitoes, poses a significant public health threat in tropical and subtropical regions worldwide. Despite efforts to control its spread through various means, including vector control strategies and vaccine development, dengue remains a formidable challenge. Mathematical modeling has emerged as a valuable tool in understanding the complex dynamics of dengue transmission and evaluating control strategies, particularly those involving biological control methods.